Combined effect of strain-rate and mode-ratio on the fracture of lead-free solder joints. (15th November 2015) - Nourani, Amir; Spelt, Jan K.
Abstract: The critical strain energy release rate for the solder joint fracture was measured as a function of the strain rate and the mode ratio of loading. These data are useful in predicting the fracture of solder joints loaded under arbitrary combinations of tension and shear during the impact conditions typical of falling portable electronic devices. In this study, strain rates from quasi-static (close to 0 s − 1 ) to 61 s − 1 were investigated at phase angles from 0 to 60°, typical of the range found in microelectronic devices. Copper–solder–copper double cantilever beam (DCB) model specimens were prepared using SAC305 solder at cooling rates and times above liquidus typical of actual ball grid arrays (BGAs). A drop tester was designed and built to achieve different strain rates at various mode ratios. The critical initiation strain energy release rate, Jci, increased about 70% from quasi-static to intermediate strain rates, before decreasing by more than 67% from intermediate strain rates to 42 s − 1 . Graphical abstract: Highlights: Solder joints were prepared using process conditions typical of ball grid arrays. A drop tester was used to achieve various phase angles at high strain rates. Increasing phase angle increased the initiation fracture energy at all strain rates. Fracture energy exhibited a maximum as strain rate increased from quasi-static range.